2017
DOI: 10.3354/cr01454
|View full text |Cite
|
Sign up to set email alerts
|

Human-environment dynamics in European treeline ecosystems: a synthesis based on the DPSIR framework

Abstract: The state of, and changes to, altitudinal and polar treeline ecosystems and their services in selected mountain regions in Europe were analyzed using the drivers-pressures-stateimpacts-responses (DPSIR) framework. The analysis was based on 45 responses of experts from 19 countries to 2 semi-structured questionnaires on treeline ecosystem services (ESs), stakeholders and the DPSIR factors, and 11 case study descriptions of best management practices. The experts recognized climate and land-use changes as the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…As the number of animals decreased, the remaining animals covered their requirements in more accessible areas of lower altitude. Kyriazopoulos et al (2017) have reported similar results, especially for the Pindos Mountain treeline ecotones, where Juniperus spp. encroachment has been witnessed in formerly grazed rangelands.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…As the number of animals decreased, the remaining animals covered their requirements in more accessible areas of lower altitude. Kyriazopoulos et al (2017) have reported similar results, especially for the Pindos Mountain treeline ecotones, where Juniperus spp. encroachment has been witnessed in formerly grazed rangelands.…”
Section: Resultssupporting
confidence: 64%
“…encroachment has been witnessed in formerly grazed rangelands. In the last decades, there is an upward increase of treelines as anthropogenic activities have been decreased (Ameztegui et al, 2016;Kyriazopoulos et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of climate change and the connected land use change on biodiversity and ecosystem services provision in several European countries is summarized by Wielgolaski et al (2017), and Kyriazopoulos et al (2017) (both this Special), and Sarkki et al (2016). One of the possible adaptive management options in response to climate change, assisted migration as human-assisted movement of species, has been frequently debated in the last few years (SteMarie et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid pace of globalization and economic growth has brought urban development to the forefront, necessitating a paradigm shift towards sustainability in urban settlements [1][2][3]. Sustainability in this context encompasses thoughtful consideration of Environmental, Social, and Governance (ESG) elements and examines various components of demographic, environmental, social, economic, transportation, and ecologic features of an area [4][5][6], acknowledging their intricate interplay and their far-reaching impact on the urban ecosystem on both short-and long-term horizons. Ultimately, sustainability in urban development aims to create livable and friendly places that are not only habitable but also nurturing for current and future generations.…”
Section: Introductionmentioning
confidence: 99%